Contracting over commitment vs. flexibility under asymmetric information - Simone Galperti (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2011)
We study a dynamic model of monopolistic provision of commitment devices to sophisticated, Strotzian decision makers. We allow for unobservable heterogeneity at the contracting stage in the agents' preferences for commitment vs. flexibility. The first-best contracts under complete information allow to successfully commit to the optimal level of flexibility. Importantly, this outcome is robust to small amounts of unobservable heterogeneity. When individuals differ substantially in their self control, under asymmetric information highly time-inconsistent agents exert a positive externality on low time-inconsistent fellows. Its magnitude depends on the degree of contractual flexibility and the likelihood of facing temptation. We derive the optimal screening mechanism and characterize its distortions. We analyze the inefficiency of the monopolist's offers in terms of the induced balance between commitment and flexibility.
Keywords: D42; D62; D82; D86; D91; G21; G23; 330; time inconsistency; self-control; commitment; flexibility; contracts; screening; information externalities